Peningkatan Hasil Belajar Dengan Menggunakan Media Digital dalam Membaca Al-Qur’an di SDN 26 Taratak Baru - Madarmis, Osra (EduSpirit : Jurnal Pendidikan Kolaboratif, 2025)
This study aims to improve the learning outcomes of fourth-grade students at SDN 26 Taratak Baru in Islamic Education subjects through a Project-Based Learning (PJBL) approach utilizing digital media. The research was conducted in two cycles, each consisting of planning, implementation, observation, and reflection stages. The results indicated a significant improvement in student learning outcomes. In the first cycle, the learning mastery level reached 60%, which increased to 87% in the second cycle. Digital media proved effective in enhancing students' understanding of Q.S At-Tiin and the hadith about kinship, as well as increasing engagement and motivation. However, challenges such as limited guidance in using digital media and uneven student motivation remain. This study concludes that PJBL with digital media is effective in improving student learning outcomes and is relevant for supporting education in the digital era.